2015
DOI: 10.18517/ijaseit.5.5.560
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Semi-Dwarf Allele Mutants Segregation Pattern as the Result of Gamma Ray Irradiation of West Sumatera Black Rice

Abstract: Black rice is a local rice originating from East Pasaman which has a low yield potential, long panicles, too high of longevity and plant height and soeasily fall. To reduce plant height has been irradiated rice seedsas much as 200 grams of black rice with a dose of 200 Gy of gamma rays. This study aimed to obtain information about the frequency of mutant semi-dwarf/dwarf and segregation patterns in mutant alleles black rice as the genetic improvement of West Sumatra local rice through mutation induction. From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
2
0
1
Order By: Relevance
“…Rice's plant height and seed fertility percentage declined with linear trend along with enhancement of gamma radiation doses starting from 100 Gy to 350 Gy (Sasikala & Kalaiyarasi, 2010). In addition, the application of 200 Gy gamma ray radiation created genetic changes in black rice in term of plant height (Warman, Suliansyah, Swasti, Syarif, & Alfi, 2015). This result was in line with other experiment which revealed that 200 Gy gamma ray decreased the plant height of Cempo Ireng black rice (Masruroh, Samanhudi, Sulanjari, & Yunus, 2016).…”
Section: Copyright © 2019 Universitas Brawijayasupporting
confidence: 87%
“…Rice's plant height and seed fertility percentage declined with linear trend along with enhancement of gamma radiation doses starting from 100 Gy to 350 Gy (Sasikala & Kalaiyarasi, 2010). In addition, the application of 200 Gy gamma ray radiation created genetic changes in black rice in term of plant height (Warman, Suliansyah, Swasti, Syarif, & Alfi, 2015). This result was in line with other experiment which revealed that 200 Gy gamma ray decreased the plant height of Cempo Ireng black rice (Masruroh, Samanhudi, Sulanjari, & Yunus, 2016).…”
Section: Copyright © 2019 Universitas Brawijayasupporting
confidence: 87%
“…The plant height and productive tillers being essential agronomic characters and important identity of the genotype. Reference [26] reported that plant height characters being influenced by one or two allele groups, of which one allele controlled the semi-dwarf, while the other one controlled the plant height character. The Sriwijaya/N148+ crossbreed height averagely 118.5 cm, while the Sriwijaya/IR7858-1 crossbreed height averagely 109.7 based on the SES IRRI [19], while the ideal plant characteristics according to [27] for the plant height averagely 115-120 cm.…”
Section: Agronomic Character Appearance Of the Selected Drought Tomentioning
confidence: 99%
“…Sejumlah bukti menunjukkan bahwa iradiasi benih dan bagian vegetatif tanaman dengan sinar gamma, dalam kisaran 1-20 Gy mempercepat proses pertumbuhan dan perkembangan (Katiyar et al, 2022). Peningkatan yang dimediasi sinar gamma dalam atribut seperti persentase perkecambahan, panjang tunas akar, jumlah malai, panjang malai, jumlah biji per malai, dan sifat fitokimia telah dijelaskan dalam Harding et al, (2012);Islam et al, (2014);Henny Puspita Sari, Irfan Suliansyah, Aswaldi Anwar, Indra Dwipa., Kajian: Pengembangan Varietas Unggul Baru Padi (Oryza sativa L.) Lokal melalui Iridasi Gamma Warman et al, (2015); Kadhimi et al, (2016);Gowthami et al, (2017); Tiwaria et al, (2018); Lalitha et al, (2019); Imam & Chakraborty, (2019); Kato et al, (2020);Andrew-Peter-Leon et al, (2021);Gowthami et al, (2021). Hasil penelitian Andrew-Peter- Leon et al, (2021), generasi M6 pada populasi mutan manghasilkan hari berbunga lebih cepat (11,81%), menurunkan tinggi tanaman hingga 40%, dan meningkatkan hasil per tanaman sebesar 45,73%.…”
Section: Respons Morfo-fisiologisunclassified